Transformasi Digital: Peran E-Commerce dalam Meningkatkan Daya Saing Bisnis di Indonesia - Marginingsih, Ratnawaty; Susilowati, Isnurrini Hidayat; Sari, Imelda; Widiyanti, Wiwik (Indo-Fintech Intellectuals: Journal of Economics and Business, 2025)
Digital transformation in Indonesia has driven significant growth in the e-commerce sector, making it a key driver of business competitiveness in local and global markets. This study aims to analyze the role of e-commerce in increasing business competitiveness in Indonesia using descriptive-qualitative methods. Data was obtained through literature studies, secondary data analysis from reports from the Ministry of Trade, the Central Statistics Agency (BPS), and related scientific publications. The results of the study show that the MSME sector dominates the business structure in Indonesia with the majority of businesses having an annual turnover of less than 2 billion rupiah. However, there is an opportunity to increase the business scale of MSMEs into medium and large enterprises through capacity building programs and access to financing. The use of e-commerce has great potential to increase business competitiveness in Indonesia, but stronger collaboration between the government and the private sector is needed to create an inclusive and sustainable digital ecosystem